Tor vergata Synoptic Solar Telescope: preliminary optical design and spectral characterization. (May 2020) - Calchetti, D; Viavattene, G; Berrilli, F; Moro, D Del; Giovannelli, L; Oliviero, M
Abstract: Synoptic telescopes are fundamental tools in solar physics. They are tipically used for high cadence full-disk observations of the Sun at different wavelengths, in order to study the solar activity across the solar cycle. The TSST ( Tor vergata Synoptic Solar Telescope ) is a new synoptic telescope composed of a Ha filter-based telescope centered at 656 nm and a custom Magneto Optical Filter (MOF)-based telescope centered in the potassium (KI D1) absorption line at 770 nm. Observations of the Ha line are important for the detection of flaring regions and to track the Sun during the acquisition. The aim of the telescope is to monitor the solar activity using the line of sight (LoS) magnetograms and dopplergrams of the solar photosphere produced by the MOF-based telescope. Magnetograms are essential for the study of the geometry of the magnetic field in active regions, while dopplergrams can be used to study the dynamics of the solar lower atmosphere. In this work, we focus our attention on the custom MOF-based telescope. Firstly, we present the optical design of the instrument. It is a refractor telescope with a 80 mm aperture and an effective focal length of ∼1m. We also present details on the preliminary spectral characterization of this instrument at different cell temperatures, which is a mandatory step to calibrate magnetograms and dopplergrams. The results obtained during this first test are in agreement with the peaks separation (∼200 mÅ) and FWHM (∼ 50 mÅ) that we expected.